An investigation on predictors of life satisfaction among the elderly - Eshkoor, Sima Ataollahi; Tengku Abdul Hamid, Tengku Aizan; Chan, Yoke Mun; Shahar, Suzana (International Organization Center of Academic Research, 2015)
In the elderly, the perception of life satisfaction and quality of life are related to many factors such as healthy life-span, chronic illnesses, expectations and self-perception of ageing. This study aimed to determine the effects of variables including age, employment, education, cognition, ethnicity, debt, sex differences, intimacy capability, sleep hours, taking salary, home ownership status, and living with a partner on life satisfaction in the Malaysian elderly. This project recruited 2322 subjects who were non-institutionalized Malaysian elderly aged 60 years and above. Life satisfaction was measured by asking in general ‘Are you satisfied with your current life’. The multiple logistic regression analysis was used to predict the effects of susceptible variables on life satisfaction in subjects. Approximately, 90.4 % of samples reported that they were satisfied with their current life. The results of multiple regression analysis showed that ethnic Malay (odds ratio [OR] = 1.50; p = 0.014), and living with a partner (OR = 1.51; p = 0.015) were significantly associated with the higher level of life satisfaction in respondents (p<0.05). Age, employment, cognition, debt, education, taking salary, intimacy capability, sex differences, sleep hours, and home ownership status did not show any significant effects on life satisfaction in subjects (p>0.05). It was concluded that ethnic Malay and living with a partner prominently enhanced the level of life satisfaction in respondents.